Time-resolved Coulomb-explosion imaging of nuclear wave-packet dynamics induced in diatomic molecules by intense few-cycle laser pulses - Bocharova, I. A.; Alnaser, A. S.; Thumm, U.; Niederhausen, T.; Ray, D.; Cocke, C. L.; Litvinyuk, I. V. (My University, 2011)
We studied the nuclear dynamics in diatomic molecules (N2, O2, and CO) following their interaction with intense near-IR few-cycle laser pulses. Using Coulomb-explosion imaging in combination with the pump-probe approach, we mapped dissociation pathways of those molecules and their molecular ions. We identified all symmetric and asymmetric breakup channels for molecular ions up to N5+2, O4+2, and CO4+. For each of those channels we measured the kinetic energy release (KER) spectra as a function of delay between the pump and probe pulses. For both N2 and O2 the asymmetric (3,1) channel is only observed for short (<20 fs) delays and completely disappears after that. We interpret this observation as a signature of electron localization taking place in dissociating molecular tri-cations when their internuclear separation reaches about 2.5 times the equilibrium bond length. This is a direct confirmation that electron localization plays an essential role in the universal mechanism of enhanced ionization in homonuclear diatomic molecules. Using classical and quantum mechanical simulations of the time-dependent KER spectra, we identify the pathways and intermediate states involved in the laser-induced dissociation of those molecules.